Feminism with a Good Laugh – Holberg, Irony, and Equal Rights - Bredsdorff, Thomas (Scandinavistica Vilnensis, 2014)
Ludvig Holberg was a serious feminist throughout his career. Unlike most Enlightenment philosophers, he insisted on extending the enlightened principle of equal rights to women. He was also a gifted ironist, and employed laughter in his quest for equality, which could be one reason why his feminism has not always been taken seriously. An attempt is made to place Holberg’s irony in a historical perspective, as compared with romantic irony and Kierkegaard’s notion of that intriguing concept.